Shallow subtidal macroalgae in the North-eastern Atlantic archipelagos (Macaronesian region): a spatial approach to community structure - Sangil, Carlos (2021)
Shallow subtidal macroalgal communities in the North-eastern Atlantic archipelagos (Azores, Madeira, Canaries and Cape Verde) were studied in order to identify their spatial organization patterns and the main drivers of change. Fifteen islands and 145 sites across 15º of latitude and 2850 km were sampled. We found high spatial variability across the scales considered (archipelago, island and site). The structure of macroalgal communities differed among archipelagos, except between Madeira and the Canaries, which were similar. Across a latitudinal gradient, macroalgal communities in the Azores were clearly separated from the other archipelagos; communities in Madeira and the Canaries occupied an intermediate position, while those in Cape Verde appeared at the opposite end of the gradient. In the Azores, species with warm-temperate affinities dominated commu nities. Cape Verde communities were, in contrast, dominated by tropical taxa, whereas in the subtropical Canaries and Madeira there was a mixture of species with colder and warmer affinities. Apart from crustose coralline algae, the Dictyotales were the group with greatest cover; larger and longer-lived species were progressively replaced by short-lived species along a latitudinal gradient from north to south. The perennial species Zonaria tournefortii dominated the sea-bottom in the Azores, the semi perennial Lophophora variegata in the Canaries, the filamentous algae in Madeira and the ephemeral Dictyota dichotoma in Cape Verde. We hypothesized that the differences among archipelagos could be explained by synergies between temperature and herbivory, which increased in diversity southwards, especially in Cape Verde. This was supported by the predominance of non crustose macroalgae in the Azores and of crustose macroalgae in Cape Verde, as would be predicted from the greater herbivore activity. At the scale of islands and sites, the same set of environmental variables drove differences in macroalgal community structure across all the Macaronesian archipelagos.